2006
DOI: 10.1029/2005gb002676
|View full text |Cite
|
Sign up to set email alerts
|

Large accumulation of anthropogenic CO2 in the East (Japan) Sea and its significant impact on carbonate chemistry

Abstract: [1] This paper reports on a basin-wide inventory of anthropogenic CO 2 in the East (Japan) Sea determined from high-quality alkalinity, chlorofluorocarbon, and nutrient data collected during a summertime survey in 1999 and total dissolved inorganic carbon data calculated from pH and alkalinity measurements. The data set comprises measurements from 203 hydrographic stations and covers most of the East Sea with the exception of the northwestern boundary region. Anthropogenic CO 2 concentrations are estimated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 59 publications
2
57
0
Order By: Relevance
“…Annually varying global air-sea CO 2 flux estimates are based on empirical approaches relating in situ measurements with satellite observations of wind and sea surface temperature (Sabine et al 2008(Sabine et al , 2009(Sabine et al , 2010. The latest empirical approach for quantifying the air-sea CO 2 exchange utilizing in situ, climatological, and satellite data from 1982 to 2007 is described in Park et al (2010). Gruber et al (2009) estimate that the pre-industrial steady state ocean was a source of 0.45 Pg C yr -1 , the estimated average net flux equates to an ocean anthropogenic CO 2 uptake of 1.92 Pg C yr -1 , at the lower end of the range of estimates (1.8 Pg C yr -1 -2.4 Pg C yr -1 ) recently summarized by Gruber et al (2009).…”
Section: ) Atlantic Oceanmentioning
confidence: 99%
“…Annually varying global air-sea CO 2 flux estimates are based on empirical approaches relating in situ measurements with satellite observations of wind and sea surface temperature (Sabine et al 2008(Sabine et al , 2009(Sabine et al , 2010. The latest empirical approach for quantifying the air-sea CO 2 exchange utilizing in situ, climatological, and satellite data from 1982 to 2007 is described in Park et al (2010). Gruber et al (2009) estimate that the pre-industrial steady state ocean was a source of 0.45 Pg C yr -1 , the estimated average net flux equates to an ocean anthropogenic CO 2 uptake of 1.92 Pg C yr -1 , at the lower end of the range of estimates (1.8 Pg C yr -1 -2.4 Pg C yr -1 ) recently summarized by Gruber et al (2009).…”
Section: ) Atlantic Oceanmentioning
confidence: 99%
“…Since the industrial revolution, the surface ocean pH has dropped by 0.1 units (Caldeira and Wickett, 2003) and is projected to drop another 0.3 ito 0.4 units by 2100 (Feely et al, 2004;Orr et al, 2005). The increase of anthropogenic CO 2 has led to the shallower carbonate saturation horizon of several hundred of meters in the Japan Sea (Park et al, 2006). Several laboratory studies have shown that reduction in levels of CaCO 3 saturation reduces calcification in marine calcifiers, such as calcifying phytoplankton (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The average depth of the East Sea is 1740 m, and it connects to the western North Pacific through four shallow straits with depths less than 140 m. Because of the shallow depths of these straits, subsurface waters below the thermocline (located at about 100 ~ 200 m) cannot be directly exchanged between the East Sea and North Pacific. Due to high biological productivity and accumulation of anthropogenic CO 2 (Yamada et al 2005; Park et al 2006;Yoo and Park 2009), the East Sea could be an important marginal sea in which to study oceanic carbon cycles. However, relatively few studies have investigated sea-air CO 2 fluxes in the southwestern part of the East Sea, the Ulleung Basin (Oh 1998;Kang 1999;Choi et al 2011).…”
Section: Introductionmentioning
confidence: 99%